Prognostic Value of Serum Fibrinogen Level in Determining the Severity of Appendicitis Inflammation in Adult and Pediatric Patients Undergoing Appendectomy in Two Local Centres in Tehran - Jahangiri, Fariba; Nasiri, Seyyed Javad; Negahi, Alireza; Nouhifard, Bahman; Farazmand, Behnood; Hoseini, Mostafa (International Journal of Child Health and Nutrition, 2019)
Background: Despite the recent advancements, negative appendectomy cases are notable, especially in children. We evaluated the prognostic value of serum fibrinogen level for the prediction of the severity of acute appendicitis. Methods: A cross-sectional study of children and adults who had undergone appendectomy at Ali Asghar and Rasool-e Akram hospitals, Iran, was performed. Before surgery, serum fibrinogen level was assessed by using the Clauss technique. Finally, serum fibrinogen was compared between the two groups of complicated acute appendicitis and uncomplicated ones. Results: In the adult’s complicated and uncomplicated appendicitis, no significant differences were noted in gender distribution, WBC count, and segment levels. Serum fibrinogen and C-reactive protein levels in children with complicated appendicitis were significantly higher than those in the uncomplicated ones. Serum fibrinogen level of 450 mg/dl was the optimum cut-off for predicting the severity of appendicitis in children. Serum fibrinogen level in adults with the complicated appendicitis was significantly higher than the uncomplicated appendicitis group. Also, 530 mg/dl was found the best serum fibrinogen cut-off to predict the severity of appendicitis in adults. Conclusion: Serum fibrinogen level is an appropriate diagnostic marker for the distinction of acute complicated appendicitis from uncomplicated appendicitis in children and adults.